Conceptual Framework of Green Infrastructure Performance Evaluation for Local Authority - Bilal, Kamalludin; Ali, Hishammudin Mohd; Sipan, Ibrahim; Ali, Nurlaila; Abas, Norwahidah (International Journal of Sustainable Development & World Policy, 2014)
Green infrastructure planning has grown in prominence since it was first discussed in the late 1990’s. Since the President’s Council on Sustainable Development discussed the concept researchers and academics from across the globe, though predominantly the UK, Western Europe and North America, have won the process. Green infrastructure is an important trust in National Landscape Policy (NLP). Malaysia is moving towards to a developed nation by the year 2020. An environmental requirement should be take into accounts to emphasize to ensure the planned development. The government to intensify efforts to raise awareness and participation in issues of global warming carries out efforts extensively, green technology is the discourse is often featured. The preservation of green spaces in urban areas can function as recreational and social interaction areas in engaging the citizens who peaceful, harmonious, unified, and healthy. However, the approach to Green Infrastructure in Malaysia is still at an early stage, but these efforts have actually started to walk among scholars and researchers to disentangle the appropriate method with the situation in Malaysia. The purpose of this paper is to discuss a conceptual framework in order to bring the context of facility management. This is also the way to get the performance evaluation for green infrastructure criteria for local authorities in Malaysia.